(untitled) (Journal of Special Education and Rehabilitation, 2013)
This study examines Deaf/hard of hearing college students’ implicit and explicit self-esteem, with thirty-six 18 to 21 year old (Age ± SD, 19.4±0.9) subjects. Following are the results of this study: Just as hearing students, Deaf/hard of hearing students also have significant implicit self-esteem effect; none of the observed correlations with explicit esteem is significant for either attributive IAT or the affective IAT; Implicit self-esteem of males is higher than that of females; No significant correlation exists between implicit self-esteem and the level of depression. Social comparisons and negative evaluations and attitudes of others always tend to damage explicit self-esteem of Deaf/hard of hearing students. However, positive self-attitude characterizations still exist in their self-schema.